2008
DOI: 10.1021/jf073060y
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Soybean Oil Bodies Using Protective Pectin Coatings Formed by Electrostatic Deposition

Abstract: Soybeans contain oil bodies that are naturally coated by a layer of phospholipids and proteins. In nature, this coating protects the oil bodies from environmental stresses and could be utilized by food manufacturers for the same purpose. However, natural oil bodies are physically unstable to aggregation because of the relatively weak electrostatic repulsion between them, which limits their application in many foods. In this study, oil bodies were extracted from soybean using an aqueous extraction method and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 23 publications
3
53
0
3
Order By: Relevance
“…These measurements indicated that increased amount of anionic carrageenan molecules adsorbed to the surfaces of the cationic oil bodies at pH 3 and 4 until reaching a saturated state as the carrageenan concentration was increased. Similar results were reported by Iwanaga et al (2008). At these higher carrageenan concentrations (0.08-0.5 wt.%), the electrical charge in the emulsions stabilized with λ-carrageenan was a higher constant value (around − 45 and −50 mV at pH 3 and 4, respectively), followed by that in the emulsions stabilized with ι-carrageenan (around −42 and − 50 mV at pH 3 and 4, respectively) and then κ-carrageenan (around −38 and − 40 mV at pH 3 and 4, respectively).…”
Section: Influence Of Ph and Carrageenan Type On Droplet Charge Of Sosupporting
confidence: 94%
See 1 more Smart Citation
“…These measurements indicated that increased amount of anionic carrageenan molecules adsorbed to the surfaces of the cationic oil bodies at pH 3 and 4 until reaching a saturated state as the carrageenan concentration was increased. Similar results were reported by Iwanaga et al (2008). At these higher carrageenan concentrations (0.08-0.5 wt.%), the electrical charge in the emulsions stabilized with λ-carrageenan was a higher constant value (around − 45 and −50 mV at pH 3 and 4, respectively), followed by that in the emulsions stabilized with ι-carrageenan (around −42 and − 50 mV at pH 3 and 4, respectively) and then κ-carrageenan (around −38 and − 40 mV at pH 3 and 4, respectively).…”
Section: Influence Of Ph and Carrageenan Type On Droplet Charge Of Sosupporting
confidence: 94%
“…The method changed interfacial composition by coating charged lipid droplets with a layer of oppositely charged polysaccharides to improve the stability of these emulsions. The method for improving the stability of soybean oil bodies by coating with a pectin layer has also been proved to be feasible by Iwanaga, Gray, Decker, Weiss, and McClements (2008). However, little work has been done on the stability of soybean oil bodies by coating with the polysaccharides of different molecular characteristics (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Structurally, oleosomes consist of a triacylglyceride matrix encapsulated by a monolayer of phospholipids in which oleosins proteins are embedded (Huang, 1992). Oleosomes are remarkably stable in cells because of the electronegative repulsion provided by oleosins proteins on their surface (Iwanaga, Gray, Decker, Weiss, & McClements, 2008;Tzen, Lie, & Huang, 1992). In nature, oleosins provide the oil bodies with physical and chemical protection against moisture, temperature fluctuation and the presence of oxidative reagents (Iwanaga et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Soybean typically has a protein content of approximately 34% to 42% (Wolf and others 1982) and a lipid content of approximately 20% (Seal and others 2008) which is primarily located in subcellular oil bodies (Allen and Tao 2007; Iwanaga and others 2008). Oil bodies are storage organelles within seeds and are formed of small droplets of oil surrounded by a half unit membrane of phospholipid and protein, that package the oil for optimum stability during dry storage and mobilization during seed germination (Murphy and others 2001).…”
Section: Introductionmentioning
confidence: 99%